The Relic Fluvial-Dominated Morphology of Mahakam Delta - Salahuddin Salahuddin (Berita Sedimentologi, 2011)
The Mahakam Delta lies at the mouth of the Mahakam River on the east coast of Kalimantan, about 50 km south of the equator. Geologically, the delta is located in the Kutai Basin, one of the major hydrocarbon provinces of Indonesia since the end of the 19th century.This short article attempts to present another sedimentologist’s point of view on looking at the deltaic morphology, as supported by quantitative analysis of controlling factors. Primary data on submerged morphology of the Mahakam Delta was detailed by 381 bathymetric echosounder (using a single frequency portable Raytheon DE719D MK2) survey lines that transversed all the channels as far as 10 kilometers to the offshore, with an accuracy of about 0.5% of the indicated depth, collected during two years from 2003 to 2004.